Pengaruh Stres Kerja, Motivasi Instrinsik Dan Manajemen Koping Terhadap Kinerja Pegawai Palang Merah Indonesia (PMI) - Kholisul Fuad; Henry Sudiyanto (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
The Indonesia Red Cross (IRC) as an independent government institution is required to provide the best and quality service to the community. The average working hours of workers in Indonesia reached 43 hours per week in 2015-2018, in 2019 decreased to 42 hours per week. The results of the preliminary study that the age of employees ranged from 20-64 y.o, high school and collage levels, 60% of employees experienced work stress, 60% had low intrinsic motivation. The purpose was to analyze the influence of work stress, intrinsic motivation and coping management on the performance of employees of the Indonesia Red Cross (IRC) Malang City. The observational type correlation analysis research method with a cross-sectional approach, the population of all IRC employees in December 2023 were 128 people, a sample were 97 people, consecutive sampling techniques, Job Stress Scale questionnaire instruments, The Work Intrinsic Motivation Theory, The Ways of Coping, Individual Work Performance Questionare, multiple linear regression data analysis with SPSS. The results that the average age was 33.84 y.o, 55.7% were women, 72.2% were educated in 3rd Diploma and Bachelor, 58.8% had a working period of > 5 years. F value 0.000 < ? 0.05, the R-Square value of 0.700 that the proportion of the influence of work stress, intrinsic motivation. coping management on employee performance variables is 70%, while the remaining 30% is influenced by other variables. Conclusion, there is an influence of work stress, intrinsic motivation and coping management on employee performance